Preferred Social Networking App by Employees in Tourism and Hospitality Industry in Kenya - Francis, Kabii; Jilo, Naghea (Journal of Tourism Management Research, 2021)
The purpose of this paper was to examine the preferred social media application network by employees in the tourism and hospitality industry. The specific aims were to examine the preferred social media amongst Facebook, WhatsApp, Twitter, Instagram, LinkedIn, email and YouTube, examine the relationship between respondent’s gender, a position at workplace and choice of social media and finally find out official the duties performed by the respondent’s using the smartphones. The finding indicated that the most popular social media platform was WhatsApp (93%) closely followed by Email (84%) and the least being LinkedIn used by only 25% of respondents. Employees’ gender (χ2=5.880, df =1, p<0.05) and position at the workplace (χ2=9.585, df =2, p<0.05) had minimal influence on the selection of social media preference. The majority (81 %) of the respondents perform up to 50% of their official duties with the help of their smartphones translating to improved and effective customer services, reduced operation cost, and healthier business performance. The study concluded that WhatsApp and Email were the most preferred social media network and were used to communicate and transact business with customers and other stakeholders in the tourism and hospitality industry. Smartphones are no longer luxury tools but are part of the technology that every employee in the industry must adapt to.